2003
DOI: 10.1111/1468-2508.00209
|View full text |Cite
|
Sign up to set email alerts
|

Political Responsiveness and Equity in Public Education Finance

Abstract: This study explores how politics affects the propensity of the American states to pursue equity in local outcomes. Using state education finance as an object of analysis, we develop a theoretical model that emphasizes the social welfare implications of equity versus allocative efficiency and distributive politics. We then hypothesize that the relative liberalism of a state's citizens and institutions should affect the weight attached to equity in the social welfare function, as well as the ability of the court… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…The underlying continuum for both indicators is conceived as operational ideology (or policy mood)-the kinds of policies preferred-rather than self-identification (or symbolic ideology) Stimson 1991). These ideology indicators have proven useful in analyzing the impact of public opinion or the policy preferences of elected officials on a wide variety of state policy outputs, including welfare reform (Soss et al 2001), antismoking legislation (Shipan and Volden 2006), educational allocations to local school districts (Wood and Theobald 2003), penal legislation (Langer and Brace 2005), judicial decisions (Songer and Ginn 2002), and economic regulation (Kim and Gerber 2005). The BRFH indicators of state ideology have also been employed as independent variables in studies of partisan conflict in state legislatures (Fiorina 1999;Meinke and Hasecke 2003) and cooperation between federal and state agencies in grant programs (Nicholson-Crotty 2004).…”
mentioning
confidence: 99%
“…The underlying continuum for both indicators is conceived as operational ideology (or policy mood)-the kinds of policies preferred-rather than self-identification (or symbolic ideology) Stimson 1991). These ideology indicators have proven useful in analyzing the impact of public opinion or the policy preferences of elected officials on a wide variety of state policy outputs, including welfare reform (Soss et al 2001), antismoking legislation (Shipan and Volden 2006), educational allocations to local school districts (Wood and Theobald 2003), penal legislation (Langer and Brace 2005), judicial decisions (Songer and Ginn 2002), and economic regulation (Kim and Gerber 2005). The BRFH indicators of state ideology have also been employed as independent variables in studies of partisan conflict in state legislatures (Fiorina 1999;Meinke and Hasecke 2003) and cooperation between federal and state agencies in grant programs (Nicholson-Crotty 2004).…”
mentioning
confidence: 99%
“…In contrast, appointed or ex officio board trustees will likely be more aligned with the political interests of elected officials (Chen ; Moe ). For elected officials, the policies they pursue should reflect public opinion and voter preferences (Jacoby and Schneider ; Wood and Theobald ). As Anzia and Moe () point out, prior to the Great Recession, public interest in public pension benefits was minimal.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…For instance, Hill and Leighley (1992) demonstrated a link between the cultural conservatism of a state's citizens and state welfare payments. Meier and McFarlane (1992) showed that abortion funding within a state is a function of the relative liberalism of a state's congressional delegation, while Wood and Theobald (2003) demonstrated the link between the conservatism of a state's citizens and state revenue allocations to school districts (these allocations are also a function of the actions of both court and legislative action).…”
Section: The Political Environmentmentioning
confidence: 99%